Análise de protocolos de roteamento em Vanets de diferentes densidades em ambientes urbanos - Ferronato, Jair José (2015)
The networks are present in our daily lives and have essential role in communication processes. The Vehicular Ad hoc Networks (VANETs) are vehicular networks and data exchange between vehicles and with the highway infrastructure for data transmission. This work presents the simulation of vehicular networks protocols based at topology and by comparing the behavior and performance of data transmission in the urban setting in the city of Passo Fundo. Actual parameters were used as scenario definition in the central area of the city, average speed allowed on site, flow of vehicles that travel at certain times in order to apply the concepts of the literature on carrier networks. Therefore, the research sought to analyze the behavior of protocols assigned to simulation with Network Simulator 2 (NS2) and the variation of density of nodes present on the network. The results of this survey showed that the reactive Protocol Ad hoc On Demand Distance Vector (AODV) gained advantage over the proactive protocol Optimized Link State Routing Protocol (OLSR) and hybrid Zone Routing Protocol (ZRP). On the other hand, the proactive Protocol obtained satisfactory results for use with delay-sensitive applications, for example, applications with real-time features. The hybrid Protocol obtained satisfactory results for applications with variation of vehicular density and can even be improved and adapted to current conditions or data transmission, too, can be created new protocols for best results in vehicular networks